1997
DOI: 10.1258/1357633971930364
|View full text |Cite
|
Sign up to set email alerts
|

Telepsychiatry, the satellite system and family consultation

Abstract: A pilot telepsychiatry session was conducted with the US Department of Defense Satellite Communication System. The subjects were a family incompletely divorced many years before. There were two satellite interviews with this family. Bringing together all members of the original family so that questions could be addressed as to what happened when the children were very young unblocked a 13-year-old communication problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…There were seven case studies [20][21][22][23][24][25][26] and eight other reports 1,4-6,27-30 . Five of the reports were published as letters to the editor in different journals 5,21,24,27,28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were seven case studies [20][21][22][23][24][25][26] and eight other reports 1,4-6,27-30 . Five of the reports were published as letters to the editor in different journals 5,21,24,27,28 .…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 categorizes the studies according to the Quality of Evidence criteria: two were in category I, one in category II-2 and the others in category III. There were seven case reports [20][21][22][23][24][25][26] . In the five that involved the treatment of children or adolescents [20][21][22]25,26 there were 2-16 therapy sessions and the patient's condition improved; in the two that involved consultations between professionals (both for a child with conduct disorder) 23 Case report ISDN 128 kbit/s Family therapy in the treatment of anorexia nervosa Alessi 21 Case report ISDN 384 kbit/s An adolescent with major depressive disorder Rendon 25 Case report ISDN 128 kbit/s A child with a serious disruptive behaviour problem Paul 22 Case report Satellite (?)…”
Section: Resultsmentioning
confidence: 99%
“…13 A limited number of studies have also addressed child mental health applications. 14,15 Case studies with children have suggested positive effects with treatment over interactive videoconference (VC) for oppositional defiant disorder, 16 family conflict, 17 and externalizing behaviors. 18 Families and clinicians are overwhelmingly satisfied with telemental health services in the United States and across the world.…”
Section: Introduction I N the Mental Health Field Psychiatristsmentioning
confidence: 99%
“…74 Telepsychiatry Several reports in the last decade of the twentieth century revealed that telepsychiatry was coming of age. [75][76][77][78][79][80][81][82][83][84][85][86][87] Telemedicine for patients with obsessive-compulsive disorder was reported as early as 1996. 88 In 1998 Brown reported the use of telemedicine in ''rural psychiatry''.…”
Section: Dementiamentioning
confidence: 99%